Political Impersonations on Saturday Night Live during the 2016 U.S. Presidential Election - Outi J. Hakola (European Journal of American Studies)
The sketch comedy show Saturday Night Live is known for political impersonations. During the 2016 U.S. presidential election, these impersonations were widely followed and debated, and it can be argued that they had an influence on public and political discussions about the election. This article analyzes how Donald Trump and Hillary Clinton were impersonated, interpreted, and reframed on Saturday Night Live.